Diagnosis distribution in cases with granulomatous inflammation in lung, pleura, and lymph node biopsies: an experience from a tertiary level single center chest diseases and thoracic surgery hospital - Aydogan Eroglu, Selma; Yildiz, Tekin; Sonkaya, Esin; Kavas, Murat; Ozbaki, Fatma; Sertcelik, Lale; Sen, Aycim; Sevim, Tulin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Granulomatous inflammation is found in a wide range of diseases, and most commonly associated with sarcoidosis and tuberculosis. Granulomas are pathologically classified into two main groups; necrotic and non-necrotic.Objectives: The aim of this study was to evaluate the radiological, laboratory, and pathological findings of a large patient population with granuloma in biopsy samples, to determine the final diagnostic distribution.Methods: This study was designed as a retrospective, descriptive, observational, cross-sectional study. It was conducted in patients with granulomatous inflammation detected in lung, pleural, mediastinal, hilar, and/or peripheral lymph node biopsies. Demographic information, radiological, microbiological, and laboratory results of the patients were obtained via the information processing system of the hospital. The diagnoses recorded were re-evaluated by at least two experienced clinicians and the final diagnosis distributions were made.Results: A total of 392 patients were included in the study. Non-necrotizing inflammation was detected in 268 patients, and necrotizing granulomatous inflammation was found in 124 patients. The most common cause of non-necrotizing inflammation was sarcoidosis, and tuberculosis in the case of necrotizing inflammation. A total of 77.2% of sarcoidosis patients had non-necrotizing inflammation and 54.3% of the tuberculosis patients had necrotizing inflammation. In the diagnosis distribution of granulomatous inflammation sarcoidosis, mycobacterium infections (especially tuberculosis), sarcoid reaction due to malignancy, pneumoconiosis, granulomatosis with polyangiitis and hypersensitivity pneumonitis were detected, respectively. A total of 392 patients were diagnosed with 13 different diseases. We detected a small number of patients with cyst hydatid, benign fibrous histiocytoma, and cryptogenic organizing pneumonia as the causes of granulomatous inflammation.  In 15 patients (3.8%) no specific diagnosis could be made.Conclusions: The diagnosis of granulomatous inflammation detected in biopsy samples is common for clinicians and a differential diagnosis is difficult in many cases. Clinical findings, laboratory results, and radiological features should be evaluated in detail and the final decision should be made from the multidisciplinary findings. The presence of necrosis in tissue samples alone is not a reliable finding for a final diagnosis.